Selección de los animales en base a los caracteres de importancia económica en la producción de leche de bovinos acorde al objetivo de mejora genética en la parroquia de Mulaló. - Campaña Coba, Sheila Kerly (2023)
Milk production in Cotopaxi could be more efficient since around 4 liters per hectare is produced due to multiple factors, including the lack of evaluations of dairy cows. Therefore, the objective of genetic improvement for milk production in bovines in the Mulaló parish was defined according to the characteristics of economic importance. The investigation was carried out with 62 animals and 11 producers who collaborated on the project; the data collection was carried out during October, November, and December. The data of the animals were obtained by weighing, milk production control in kilograms, and udder health focused on CMT tests. As a result, the objective of genetic improvement must include milk production (20kg/day), density (1,030 g/ml), and mastitis (100% negative). Regarding the parameters of economic interest, the following results were obtained: milk production with an average of (16 kg/day), density (1,026g/ml), and mastitis (100% negative) indicating that farmers have good husbandry practices. In Milking, the average daily weight gain is 78.95 kg, considering the bovines under study were in different lactation periods. Finally, Cara Blanca, Mocha, Pirata, Café, Copito de nieve and Morena bovines were highlighted to disseminate their genetic material based on the economic importance characters, having the highest values in terms of quality analysis, health, and production of milk.